2016
DOI: 10.1016/j.clinbiomech.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Hip abductor neuromuscular capacity: A limiting factor in mediolateral balance control in older adults?

Abstract: Background: Mediolateral balance impairment is an important cause of falling in older adults. We aimed to investigate whether hip abductor muscular strength and/or position sense are limiting factors in mediolateral balance control. Methods: Sixteen community-dwelling older adults performed three different mediolateral weight-shifting tasks, by tracking (1) a sinusoidally moving visual target, "visual-MELBA"; (2) a sinusoidally translating platform without explicit visual feedback, "mechanical-MELBA"; and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…A previous study by our group also found a lower control bandwidth during MELBA in older than in young adults and with similar overall performance values (Cofré Lizama et al, 2014). This balance deterioration can partly be attributed to a decreased hip abduction-adduction strength and torque production in older adults population as these muscles are some of the main actuators in the displacement of the CoM in the frontal plane (Arvin et al, 2015;Arvin et al, 2016;Chang et al, 2005;Johnson et al, 2004). However, deterioration of other systems with ageing such as vision and attention, which are highly challenged during visual MELBA, may also have a negative effect on balance control (Maki et al, 2001;Maki and McIlroy, 2007).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…A previous study by our group also found a lower control bandwidth during MELBA in older than in young adults and with similar overall performance values (Cofré Lizama et al, 2014). This balance deterioration can partly be attributed to a decreased hip abduction-adduction strength and torque production in older adults population as these muscles are some of the main actuators in the displacement of the CoM in the frontal plane (Arvin et al, 2015;Arvin et al, 2016;Chang et al, 2005;Johnson et al, 2004). However, deterioration of other systems with ageing such as vision and attention, which are highly challenged during visual MELBA, may also have a negative effect on balance control (Maki et al, 2001;Maki and McIlroy, 2007).…”
Section: Discussionsupporting
confidence: 63%
“…This suggests that mechanical MELBA may impose a greater challenge for the balance control system requiring a change in motor strategy in both age groups to cope with the task (similar change in PS angle ). These strategies may involve an increasing use of hip musculature and trunk-legs decoupling, as seen in previous studies using surface perturbations (Arvin et al, 2016;Jilk et al, 2014). We used the average angle phase-shift (PS angle ) within PS mean as an overall measure of the strategies utilized during both tasks and both targets.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations